Long noncoding RNAs of single hematopoietic stem and progenitor cells in healthy and dysplastic human bone marrow - Wu, Zhijie; Gao, Shouguo; Zhao, Xin; Chen, Jinguo; Keyvanfar, Keyvan; Feng, Xingmin; Kajigaya, Sachiko; Young, Neal S. (Haematologica (Roma), 2019)
Long noncoding RNAs (lncRNAs) are regulators of cell differentiation and development. The lncRNA transcriptome in human hematopoietic stem and progenitor cells is not comprehensively defined. We investigated lncRNAs in 979 human bone marrow-derived CD34 cells by single cell RNA sequencing followed by transcriptome reconstruction. We identified 3,173 lncRNAs in total, among which 2,365 were previously unknown, and we characterized lncRNA stem, differentiation, and maturation signatures. lncRNA expression exhibited high cell-to-cell variation, which was only apparent in single cell analysis. lncRNA expression followed a lineage-specific and highly dynamic pattern during early hematopoiesis. lncRNAs in hematopoietic cells closely correlated with protein-coding genes of known functions in the regulation of hematopoiesis and cell fate decisions, and the potential regulatory roles of lncRNAs in hematopoiesis were imputed by projection from protein-coding genes with a "guilt-by-association" approach. We characterized lncRNAs preferentially expressed in hematopoietic stem cells and in various downstream differentiated lineage progenitors. We also profiled lncRNA expression in single cells from patients with myelodysplastic syndromes and in aneuploid cells in particular. Our study provides a global view of lncRNAs in human hematopoietic stem and progenitor cells. We observed a highly ordered pattern of lncRNA expression and participation in regulation of early hematopoiesis, and coordinate aberrant messenger RNA and lncRNA transcriptomes in dysplastic hematopoiesis. ( ).